2011
DOI: 10.1089/hum.2010.231
|View full text |Cite
|
Sign up to set email alerts
|

Disconnecting the Yin and Yang Relation of Epidermal Growth Factor Receptor (EGFR)-Mediated Delivery: A Fully Synthetic, EGFR-Targeted Gene Transfer System Avoiding Receptor Activation

Abstract: The epidermal growth factor receptor (EGFR) is upregulated within a high percentage of solid tumors and hence is an attractive target for tumor-targeted therapies including gene therapy. The natural EGFR ligand epidermal growth factor (EGF) has been used for this purpose, despite the risk of mitogenic effects due to EGFR activation. We have developed a fully synthetic, EGFR-targeted gene delivery system based on PEGylated linear polyethylenimine (LPEI), allowing evaluation of different EGFR-binding peptides in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
84
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(92 citation statements)
references
References 31 publications
(47 reference statements)
7
84
0
1
Order By: Relevance
“…These results confirm that GE11, as a free ligand, exhibits negligible affinity to the EGFR. Previous reports however, have demonstrated binding of GE11- and EGF-linked targeted liposomes to EGFR-expressing cells in vitro (15), as well as effective and specific gene delivery into EGFR expressing cells, both in vitro and in vivo , using PPGE11 (9,10,16). These results prompted us to further investigate the potencies of tethered GE11 and EGF in inhibiting the binding of [ 125 I]-EGF, when tethered to PEI-PEG.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results confirm that GE11, as a free ligand, exhibits negligible affinity to the EGFR. Previous reports however, have demonstrated binding of GE11- and EGF-linked targeted liposomes to EGFR-expressing cells in vitro (15), as well as effective and specific gene delivery into EGFR expressing cells, both in vitro and in vivo , using PPGE11 (9,10,16). These results prompted us to further investigate the potencies of tethered GE11 and EGF in inhibiting the binding of [ 125 I]-EGF, when tethered to PEI-PEG.…”
Section: Resultsmentioning
confidence: 99%
“…Conjugation of GE11 to polyethyleneimine-polyethyleneglycol (PEI-PEG-GE11, PPGE11) enabled the targeting of EGFR over-expressing tumors in vitro and in vivo (9,10). We have recently shown that local and systemic application of EGFR-targeted poly Inosine/Cytosine (PolyIC) by PEI-PEG-EGF (PP-EGF) eradicates several pre-established EGFR-over-expressing tumor models (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…10 Additionally, GE11-conjugated polyethylenimine vectors and polyethylene glycol-conjugated liposomes have been shown to be less mitogenic, and can efficiently transfect genes into cells expressing high levels of EGFR or tumor xenografts. [10][11][12][13] These studies indicated that the GE11 peptide is likely superior to EGF for clinically targeting EGFR-expressing tumors.…”
Section: Introductionmentioning
confidence: 98%
“…Due to their high overexpression, they have been extensively used as cancer cell selective targeting receptor. We have previously used a synthetic 12 amino acids peptide that has demonstrated efficient targeting of EGFR receptor and its targeting capability has been successfully validated in vitro as well as in vivo in various EGFR-overexpressing tumor cells such as A549 [38][39][40][41][42][43]. Most importantly, this peptide is capable of inducing nanoparticles cellular uptake without activating EGFR signaling pathway and therefore was included as targeting ligand in our formulation approach [44].…”
mentioning
confidence: 99%